Bedeutung der Muskelsonographie in der Detektion von Faszikulationen bei der ALS - German, Alexander; Türk, Matthias; Schramm, Axel; Regensburger, Martin (Klinische Neurophysiologie, 2023)
In amyotrophic lateral sclerosis, fasciculations are frequently present at early stages in multiple body regions which is why they were included in guidelines and diagnostic criteria. While invasive EMG recording remains indispensable for detecting acute and chronic neurogenic changes in motor unit action potentials and firing patterns as well as to confirm the presence of fasciculation potentials, muscle ultrasonography provides a highly sensitive method to rapidly and non-invasively detect fasciculations in the different body regions. In this review, we summarize current data on the use of muscle ultrasonography for the detection of fasciculations, and we describe how muscle ultrasonography allows targeted EMG diagnosis in clinical practice. Current research studies aim to analyze fasciculations more precisely regarding their quantity and morphology, as well as their potential as a progression parameter.
CRIS-Team Scopus Importer:2023-03-31
Keywords: amyotrophic lateral sclerosis; fasciculations; muscle ultrasonography